The Impact of Psychiatric Comorbidity on Health Care Utilization in Inflammatory Bowel Disease: A Population-based Study. Issue 9 (4th December 2020) - Bernstein, Charles N; Hitchon, Carol A; Walld, Randy; Bolton, James M; Lix, Lisa M; El-Gabalawy, Renée; Sareen, Jitender; Singer, Alexander; Katz, Alan; Marriott, James; Fisk, John D; Patten, Scott B; et al.
Abstract: Background: Inflammatory bowel disease (IBD) is associated with an increase in psychiatric comorbidity (PC) compared with the general population. We aimed to determine the impact of PC on health care utilization in persons with IBD. Methods: We applied a validated administrative definition of IBD to identify all Manitobans with IBD from April 1, 2006, to March 31, 2016, and a matched cohort without IBD. A validated definition for PC in IBD population was applied to both cohorts; active PC status meant ≥2 visits for psychiatric diagnoses within a given year. We examined the association of active PC with physician visits, inpatient hospital days, proportion with inpatient hospitalization, and use of prescription IBD medications in the following year. We tested for the presence of a 2-way interaction between cohort and PC status. Results: Our study matched 8459 persons with IBD to 40, 375 controls. On crude analysis, IBD subjects had ≥3.7 additional physician visits, had >1.5 extra hospital days, and used 2.1 more drug types annually than controls. Subjects with active PC had >10 more physician visits, had 3.1 more hospital days, and used >6.3 more drugs. There was a synergistic effect of IBD (vs no IBD) and PC (vs no PC) across psychiatric disorders of around 4%. This synergistic effect was greatest for anxiety (6% [2%, 9%]). After excluding psychiatry-related visits and psychiatry-related hospital stays, there remained an excess health care utilization in persons with IBD and PC. Conclusion: Inflammatory bowel disease with PC increases health care utilization compared with matched controls and compared with persons with IBD without PC. Active PC further increases health care utilization.